PARTISIPASI PETANI DALAM PENGEMBANGAN USAHA KEHUTANAN DI DESA BELUTU KECAMATAN KANDIS - Insusanty, Enny; Suwarno, Eno (Wahana Forestra: Jurnal Kehutanan, 2021)
The research objective was to determine the level of farmer participation in forestry business development and the factors that influence farmer participation in forestry business development. This study used survey method with 32 respondents using the census of the farmers who were members of the Belutu Village farmer group. The analysis was carried out by qualitative descriptive analysis and multiple linear regression. The participation rate of forest farmers in Belutu Village was moderate, namely 46.25%, low 21.87%, 30.63% high and only 1.25% very high. The factors that influence farmer participation in forestry business in the form of pepper and honey bee cultivation were age, education, farming experience, number of family members and there was a main / part job that have very significant effect simultaneously, while all of these factors have a very significant effect. partial is the main / part job.